DC capacitor voltage stabilization for five-level NPC inverter based STATCOM under DC offset in load - Ravi Teja, S; Enamullah, Md (International Journal of Engineering and Technology, 2018)
DC voltage regulation of compensator plays a significant role in tracking performance of STATCOM. It is a common practice to employ voltage source inverter with split – capacitor topology for shunt compensator in three phase four wire systems. However, drift in each capacitor voltage is observed with the presence of dc component in zero sequence current although STATCOM control unit regulates total dc voltage, which results in poor tracking of reference current by the compensator.  An external voltage balancing circuit is identified to be a good solution to overcome this problem.  This paper proposes an improved controller for external voltage balancing circuit to restore the dc capacitors voltage. The effectiveness of the proposed control of external voltage balancing circuit is verified by simulation results showing restoration of capacitors voltage drift and there by the restoration of tracking performance of the compensator.